The central banks’ approach to digital currencies : a literature review - Ferreira, Helena Maria Cardoso (2022)
Considering the growing relevance of digital currencies and the constant speculation regarding their future, this work aims to analyze the existing literature on the treatment given by central banks to digital currencies. Adopting the form of a systematic literature review, we focus on central bank digital currencies, debating their pros and cons, and elaborating on how they should be designed. We find that the pros seem to outcome the cons, and that there is a clear preference from the authors for a retail digital currency.